Cultivation factors affecting durum wheat performance under speed breeding conditions - Bayhan, Merve; Özkan, Remzi; Albayrak, Önder; Akıncı, Cuma; Yıldırım, Mehmet (Frontiers in Plant Science, 2025)
IntroductionThis study examined the effects of pot size, soil type, fertilizer x dose interactions, and foliar fertilizer application on wheat growth under speed breeding conditions.MethodsThe study was conducted in 2020 in a semi-controlled greenhouse at Dicle University, Diyarbakır, Türkiye, with a 22-hour photoperiod, 22/17°C day/ night temperature, 70% humidity, and 316.15 µmol/m2/s light intensity using a mix of white, red, yellow, and purple LED lamps. Sampiyon durum wheat cultivar was used as plant material.ResultsThe highest productivity was achieved in a deep pot (270 cm3), 100% peat soil, and 20.20.0 (%20 N + %20 K) fertilizer application. Among the foliar fertilizer applications, the best results were observed in the tillering stage and stem elongation-heading stages.DiscussionThese findings highlight ways to optimize plant productivity and improve the efficiency of the speed breeding process. Because the primary goal of speed breeding is to obtain multiple generations in a short period, determining suitable conditions will contribute to the rapid development of more resilient and productive plant varieties in the future.